2018
DOI: 10.1088/1748-9326/aaaa99
|View full text |Cite
|
Sign up to set email alerts
|

Changing population dynamics and uneven temperature emergence combine to exacerbate regional exposure to heat extremes under 1.5 °C and 2 °C of warming

Abstract: Understanding how continuing increases in global mean temperature will exacerbate societal exposure to extreme weather events is a question of profound importance. However, determining population exposure to the impacts of heat extremes at 1.5 • C and 2 • C of global mean warming requires not only (1) a robust understanding of the physical climate system response, but also consideration of (2) projected changes to overall population size, as well as (3) changes to where people will live in the future. This ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 71 publications
4
33
0
Order By: Relevance
“…The few existing studies that performed similar analysis found that a shift from a high to a low radiative forcing pathway led to greater reduction in exposure than a shift from a high to a low population growth pathway. This holds true at the global scale (Jones et al, ) but also (i) in the United States, where Jones et al () found that a shift to a lower emission pathway or to a lower population growth pathway would reduce exposure by ~56% and ~45%, respectively; (ii) in India, where Mishra et al () showed that a shift from high to low population growth has a lower influence on exposure than a shift from +2 to +1.5 °C; (iii) in Eastern Africa, where Harrington and Otto () found that shifting from +2 to +1.5 °C would reduce exposure by ~81%, whereas shifting from a medium (SSP2) to low (SSP1) population growth pathway would reduce exposure by ~28%; and (iv) in North Africa/Middle East and Sub‐Saharan Africa, where Jones et al () demonstrated that a shift from a high (SSP3) to low (SSP5) population growth pathway would lead to a lesser reduction in exposure than a shift from a high (RCP8.5) to low (RCP4.5) emission pathway (~33–39% vs. ~47–57%). Our results—while not entirely comparable because based on different population projections, HI, and scenarios range—differ slightly from those found in the literature in that a shift from a high to a low urban population growth pathway leads to a slightly greater reduction in exposure than a shift from a high to a low emission pathway (~51% vs ~48%).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The few existing studies that performed similar analysis found that a shift from a high to a low radiative forcing pathway led to greater reduction in exposure than a shift from a high to a low population growth pathway. This holds true at the global scale (Jones et al, ) but also (i) in the United States, where Jones et al () found that a shift to a lower emission pathway or to a lower population growth pathway would reduce exposure by ~56% and ~45%, respectively; (ii) in India, where Mishra et al () showed that a shift from high to low population growth has a lower influence on exposure than a shift from +2 to +1.5 °C; (iii) in Eastern Africa, where Harrington and Otto () found that shifting from +2 to +1.5 °C would reduce exposure by ~81%, whereas shifting from a medium (SSP2) to low (SSP1) population growth pathway would reduce exposure by ~28%; and (iv) in North Africa/Middle East and Sub‐Saharan Africa, where Jones et al () demonstrated that a shift from a high (SSP3) to low (SSP5) population growth pathway would lead to a lesser reduction in exposure than a shift from a high (RCP8.5) to low (RCP4.5) emission pathway (~33–39% vs. ~47–57%). Our results—while not entirely comparable because based on different population projections, HI, and scenarios range—differ slightly from those found in the literature in that a shift from a high to a low urban population growth pathway leads to a slightly greater reduction in exposure than a shift from a high to a low emission pathway (~51% vs ~48%).…”
Section: Discussionmentioning
confidence: 96%
“…Although some recent studies have considered only maximum temperature to define the heat index ( HI ) without accounting for humidity, for example (Dong et al, ; Harrington & Otto, ; Liu et al, ), evidence suggests that humidity plays an important role in temperature discomfort and dangerous heat and thus must be integrated into the construction of the HI (Coffel et al, ; Davis et al, ; Matthews et al, ; Mora et al, ), particularly in South America, Africa, and South Asia (Russo et al, ). Various heat metrics that include both temperature and humidity have been developed over the past few years, all performing well and rather similarly (Anderson et al, ; Matthews et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risks are not just dependent on the severity of climate change and subsequent hazards but critically depend on the population's spatial distribution (exposure) and their vulnerability and capacity to prepare for and manage changing risks [5]. Increasingly studies are showing that the world's poorest are disproportionately exposed to changes in temperature extremes [6,7] and challenging hydro-climatic complexity [8][9][10]. In the water sector, between 8%-14% of the global population are expected to face severe reductions in available water resources between 1.7 • C-2.7 • C [11] and in the energy sector, more than 70% of a 'business as usual' 2050s population could expect climate sensitive changes in energy demand of +/− 5%, with negative impacts overwhelmingly in low and middle income countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…This agreement aims to keep the increase in global average temperature well below 2.0 C above preindustrial (PI) levels and to pursue ambitious targets to keep the increase to 1.5 C above PI levels. A significant body of recent studies has attempted to quantify the benefits of avoiding an additional 0.5 C increase in temperature by comparing the emerging patterns of climate change induced by global temperature increases of 1.5 and 2.0 C. Although simple thresholds based on the global average temperature are limited in their ability to represent significant regional variations (Harrington and Otto, 2018), many studies recognize the significant impact of a 0.5 C warming increase on regional climate in terms of temperature-related extremes or heat stress worldwide (e.g., King and Karoly, 2017 for Europe; Sylla et al, 2018 for West Africa; Harrington and Otto, 2018 for Southern Asia and Eastern Africa; Lee and Min, 2018;Li et al, 2018 for East Asia). These studies show that temperature responses to enhanced emissions forcings are relatively clear and straightforward.…”
mentioning
confidence: 99%